2017
DOI: 10.1007/s11914-017-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab: an Emerging Therapy in Pediatric Bone Disorders

Abstract: Purpose of Review Denosumab is an inhibitor of receptor activator of nuclear factor kappa-B ligand (RANKL), and has emerged as an important novel therapy for skeletal disorders. This article examines the use of denosumab in children. Recent findings Considerable safety and efficacy data exists for denosumab treatment of adults with osteoporosis, bone metastases, and giant cell tumors. Pediatric data is limited; however, evidence suggests denosumab may be beneficial in decreasing bone turnover, increasing bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 73 publications
(92 reference statements)
1
115
0
Order By: Relevance
“…1 Previous studies found instances of sarcomatous transformation arising in GCTBs treated with denosumab, 23,24 and there have been several suggestions regarding the ideal length of denosumab therapy and monitoring procedures. 22,[25][26][27] Further studies are required to determine the best therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies found instances of sarcomatous transformation arising in GCTBs treated with denosumab, 23,24 and there have been several suggestions regarding the ideal length of denosumab therapy and monitoring procedures. 22,[25][26][27] Further studies are required to determine the best therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab, a monoclonal antibody that blocks RANKL interaction with RANK, inhibits bone resorption by inhibiting osteoclast maturation and function. It has been approved for the treatment of osteoporosis, multiple myeloma, skeletal metastasis, and recently GCTB . RANK and RANKL expression was observed in ABCs as well as GCTBs, chondroblastoma, and myelomas using immunohistochemistry and real‐time PCR methods .…”
Section: Discussionmentioning
confidence: 99%
“…Given the severity of the initial presentation, hungry bone syndrome was anticipated despite the use of bisphosphonates, which have been implicated to reduce the risk of this postsurgical complication in patients with hyperparathyroidism . An interesting consideration in the use of denosumab, given its half‐life of 30 days and mechanism of action, is whether it might prolong postsurgical hypocalcemia. The duration and requirement for i.v.…”
Section: Discussionmentioning
confidence: 99%